Sustainability assessment of FLOCponics compared to stand-alone hydroponic and biofloc systems using emergy synthesis - Pinho, Sara M [UNESP] (2022)
FLOCponics is an intensive integrated agri-aquaculture system that combines biofloc-based aquaculture with hydroponics. Since research on FLOCponics is in its early stage of development, and many aspects of this system still need to be explored, the objective of this study was to assess and discuss the sustainability of a FLOCponics system and compare it to stand-alone biofloc and hydroponic cultures. This investigation will lead to a novel perspective of what troubling points need to be covered in the FLOCponics research field before they turn into a commercial scale problem. To do this, we conducted an experiment-based study by applying emergy synthesis to assess the sustainability of tilapia juveniles and lettuce production in FLOCponics, biofloc and/or hydroponic systems. The results indicate that the resources from the larger economy were the inputs that made the greatest contribution in all systems. Overall, most of the emergy indicators are similar for all systems, suggesting that FLOCponics, biofloc and hydroponic systems use low amounts of natural renewable resources, cause a moderate environmental load (EIR and ELR of 3.1 to 3.6), and lead to environmental stress seven times higher than the contribution to the economy (ESI of 0.3). Unit emergy values (UEVs) are different for each system, indicating that, under the evaluated conditions, FLOCponics (UEV: 2.54E + 06 sej/J) is more efficient than hydroponics (UEV: 5.55E + 10 sej/J) and less efficient than a biofloc system (UEV: 1.42E + 06 sej/J). Our findings provide valuable insights regarding the (un)sustainable aspects of FLOCponics and direct further research to improve the system's emergy performance. Based on the emergy performance, FLOCponics can be considered a promising sustainable food production approach, mainly considering that it is a system under development and there are still many opportunities for improvement.